2007
DOI: 10.1095/biolreprod.106.053736
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Deficits in Male Freshwater Turtle Chrysemys picta from Cape Cod, Massachusetts1

Abstract: Contaminated groundwater plumes have formed on the Massachusetts Military Reservation (MMR), a Superfund site on Cape Cod, Massachusetts, as a result of chemical waste disposal. The plumes are of concern to the local people who rely on groundwater as a drinking water source. We used the freshwater turtle as a sentinel species to monitor the reproductive effects of exposure and, by inference, the potential for impact on human health. Our observations of male Chrysemys picta field-trapped from Moody Pond (an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(28 reference statements)
0
13
1
Order By: Relevance
“…Alligators from Lake Apopka, FL, which is contaminated with industrial estrogenic chemicals, have smaller phalluses [10,11]. Turtles from Moody Pond, MA, exposed to xenobiotic contaminants have impaired reproductive functions [12]. Thus, perinatal exposure to estrogens has permanent, even transgenerational, deleterious effects on the development of reproductive organs in both humans and wildlife; however, mechanisms underlying these reproductive disorders are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Alligators from Lake Apopka, FL, which is contaminated with industrial estrogenic chemicals, have smaller phalluses [10,11]. Turtles from Moody Pond, MA, exposed to xenobiotic contaminants have impaired reproductive functions [12]. Thus, perinatal exposure to estrogens has permanent, even transgenerational, deleterious effects on the development of reproductive organs in both humans and wildlife; however, mechanisms underlying these reproductive disorders are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…END also causes a reduction in hatchling fractional weight (Beldomenico et al, ), thus, impaired growth could be expected. Besides, in turtles and alligators, exposure to EDCs modifies body morphometric variables (de Solla et al, ; Kitana et al, ; Moore et al, ). Unlike that reported in turtles and alligators (de Solla et al, ; Kitana et al, ; Moore et al, ), we found no differences in caiman biometric parameters after experimental exposure to EDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in turtles and alligators, exposure to EDCs modifies body morphometric variables (de Solla et al, ; Kitana et al, ; Moore et al, ). Unlike that reported in turtles and alligators (de Solla et al, ; Kitana et al, ; Moore et al, ), we found no differences in caiman biometric parameters after experimental exposure to EDCs. In turtles, exposure to several contaminants has been found to affect precloacal length in adult males of Chrysemys picta (Kitana et al, ) and Chelydra serpentina (de Solla et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of female painted turtles ( Chrysemys picta ) living near the Massachusetts Military Reservation (MMR), a Superfund site contaminated with heavy metals in Cape Cod, MA, showed reduced plasma concentrations of 17β‐estradiol and vitellogenin as compared to females from a reference site (Rie et al, 2005). Although plasma testosterone in Male turtles was similar to that of reference males, they had reduced testicular weights and sperm counts, smaller seminiferous tubule diameters, and increased germ cell apoptosis (Kitana et al, 2007). Later studies showed that cadmium concentrations in eggs from C. picta were significantly higher than from reference animals (Kitana and Callard, 2008).…”
Section: Contaminants In the Natural Environment And Effects On Wildlmentioning
confidence: 99%